Nouvelles données d'enthalpie libre de formation (ΔG°f,298) des cryptomélanes synthétiques : conséquences paragénétiques. / New determination of ΔG°f,298 of synthetic cryptomelane : paragenetic consequence - Raphael Hypolito; Rudolf Giovanoli; José Vincente Valarelli; Silvania Maria Netto (Sciences Géologiques. Bulletin, 1989)
New determination of ΔG°(f.298) of synthetic cryptomelane : paragenetic consequence Five cryptomelanes with different compositions were synthetized by oxidation (pure O₂ gas) of Mn²⁺ sulfuric solutions, and by addition of KOH, at 25°C. The following Gibbs free energies of formation were calculated from the experiments : Analytical formula — AG°f298 cryp. (kJmol"1) K0,77 MnI !1o47 MnIV7 45О i60,41H20 4 592,99 ± 1,22 K0 60 Mn 111 , 05 Mn IV7 об О i6 0,45H20 4 628,99 ± 1,21 К 0 56 Mn 111 j 23 Mn 1 v6 94 0 16 0,33H20 4 630,12 ± 1,20 К o,44 Mn 1,1 1,69 Mn ,V6 62 0 ,6 0,43H20 4 645,06 ±1,21 К0[зо Mn ni2'i8 Mn ]\29 О i6 0,53H20 4 679,58 ± 1,21 The ΔG°(f.298) cryp seems to be a function of n the number of Mn(O₂) in the cell, based on 16 oxygen as follows : ΔG°(f.298) cryp = 70,34 МпO₂ — 5.1 18,60 (kJmol"1). Correlations among Mn4+,Mn5+and K+ permitted the definition of two ideal cryptomelanes :one with a maximum of K* and Mn4* (K0,9oMnIV7 7gO 16,01) and the other with a maximum of Mn³⁺ but free of K⁺ (MnUI3 31 Mnlv5 5301б1оз)-Thermodynamic fields of stability between these two minerals with Mn²⁺ in solution were constructed in an Eh — pH diagram. Paragenetic considerations on the coexistence of cryptomelane and/or nsutite, pyrolusite and/or other minerals were obtained.